KUR Credit Scoring Assessment for Prospective Debtors to Minimize Non-Performing Loans at BPD South Sumatra Babel Main Branch Captain A.Rivai - Divaputri, Adelya; Panuntun, Bagus (CV. Rayyan Dwi Bharata, 2025)
The research entitled